2005
DOI: 10.1007/s00248-004-0030-x
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Three Bacterial Populations in Selected Streams

Abstract: The population sizes of three bacterial species, Acinetobacter calcoaceticus, Burkholderia cepacia, and Pseudomonas putida, were examined in water and sediment from nine streams in different parts of the United States using fluorescent in situ hybridization (FISH). Population sizes were determined from three sites (upstream, midstream, and downstream) in each stream to compare differences in the occurrence and distribution of the species within each stream and among streams. Physical and chemical variables m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Burkholderia spp. are found in a wide variety of niches ranging from freshwater streams and sediments to the soil rhizosphere (47,70,71). They also interact with various plants, fungi, insects, and animal pathogens (38).…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia spp. are found in a wide variety of niches ranging from freshwater streams and sediments to the soil rhizosphere (47,70,71). They also interact with various plants, fungi, insects, and animal pathogens (38).…”
Section: Discussionmentioning
confidence: 99%
“…These two sampling sites are separated by 5.2 km, which establishes the ability of water flow to partially homogenize microbial communities over at least this distance. A study of the Ipswich River (Massachusetts) demonstrated a similar degree of variability among unconnected primary stream communities (Levine and Crump 2002), and on a broader spatial scale the abundance of bacterioplankton taxa were shown to be variable among nine streams in the eastern Unites States (Olapade et al 2005(Olapade et al , 2006.…”
Section: Stream Communities and Processesmentioning
confidence: 99%
“…Nucleotide sequences of these bacteria have been detected in lakes and rivers but, so far, not in headwater streams. While substantial information on the compositions of bacterial communities in rivers and estuaries has been accumulated using fluorescence in situ hybridization (FISH) (e.g., references 7, 8, 32, 34, and 65), as well as denaturing gradient gel electrophoresis and sequence analysis (e.g., references 6, 14, 19, 33, 64, 65, and 72), fewer reports of studies of headwaters have been published, and these studies have used mainly FISH (5,12,18,22,30,49,57,56).…”
mentioning
confidence: 99%